2022
DOI: 10.3390/vaccines10050721
|View full text |Cite
|
Sign up to set email alerts
|

BCG-Based Vaccines Elicit Antigen-Specific Adaptive and Trained Immunity against SARS-CoV-2 and Andes orthohantavirus

Abstract: Background:Mycobacterium bovis Bacillus Calmette-Guérin (BCG) is a live attenuated vaccine mainly administered to newborns and used for over 100 years to prevent the disease caused by Mycobacterium tuberculosis (M. tb). This vaccine can induce immune response polarization towards a Th1 profile, which is desired for counteracting M. tb, other mycobacteria, and unrelated intracellular pathogens. The vaccine BCG has been used as a vector to express recombinant proteins and has been shown to protect against severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 83 publications
1
9
0
Order By: Relevance
“…However, the little apparent pathology, the low circulating cytokine levels, and the bacterial loads at or below the limit of detection are consistent with our unpublished work in BCG-vaccinated C57BL/6 mice. Other studies have shown that recombinant BCG vaccination in mice ( 30 ), revaccination with BCG in a clinical trial ( 31 ), and other routes of vaccination (intravenous) affect SARS-CoV-2 morbidity and mortality ( 26 ), demonstrating BCG’s unique off-target effects and potential as an adjuvant or booster. However, our study attempted to best experimentally represent what BCG’s effect would be clinically on SARS-CoV-2 given current vaccination regimens, which are intradermal and given at birth.…”
Section: Discussionmentioning
confidence: 99%
“…However, the little apparent pathology, the low circulating cytokine levels, and the bacterial loads at or below the limit of detection are consistent with our unpublished work in BCG-vaccinated C57BL/6 mice. Other studies have shown that recombinant BCG vaccination in mice ( 30 ), revaccination with BCG in a clinical trial ( 31 ), and other routes of vaccination (intravenous) affect SARS-CoV-2 morbidity and mortality ( 26 ), demonstrating BCG’s unique off-target effects and potential as an adjuvant or booster. However, our study attempted to best experimentally represent what BCG’s effect would be clinically on SARS-CoV-2 given current vaccination regimens, which are intradermal and given at birth.…”
Section: Discussionmentioning
confidence: 99%
“…This could lead to a better adaptive response or an increased innate immune response. The BCG vaccine is a promising candidate molecule against viral infections such as SARS-CoV-2 and Andes orthohantavirus, inducing a marked antigen-specific immune response [ 106 ]. Presently, there are no reliable or perfect options available for the treatment of COVID-19, as evinced by the incessant mortality and morbidity globally.…”
Section: Discussionmentioning
confidence: 99%
“…The BCG vaccine has been shown to induce heterologous lymphocyte responses against non-specific antigens by eliciting higher production of memory CD4 T-cells and CD8 T-cells to generate an effective immune response against SARS-CoV-2 [ 103 , 104 , 105 ]. Recently, it was shown that immunization with wild-type or recombinant BCG (expressing viral antigens) resulted in an enhancement of a non-specific immune response, with increased secretion of pro-inflammatory cytokines and T-cell activation upon antigenic stimulation [ 106 ]. Vaccination with BCG promoted a trained immunity profile in the immunized mice, with increased secretions of IL-6 and TNF-α, thereby contemplating a possible reality of BCG vaccines in the immune defense against non-related respiratory diseases [ 73 ] ( Figure 4 ).…”
Section: Induction Of the Activation Of Trained Immunitymentioning
confidence: 99%
“…Examples of vaccines produced under GMP regulations include those based on the innovative technique using recombinant Bacillus Calmette-Guerin (BCG), a live attenuated vaccine widely used since 1921 to prevent disease caused by Mycobacterium tuberculosis (97). This recombinant platform is capable of expressing viral particles that confer immunogenic protection against viruses such as a human respiratory syncytial virus (hRSV), human metapneumovirus (hMPV) (103-106), Andean ortho-hantavirus (ANDV), and SARS-CoV-2, the pathogen responsible for coronavirus disease 2019 (103)(104)(105)(106)(107)(108)(109)(110)(111)(112)(113)(114)(115)(116)(117)(118).…”
Section: Figurementioning
confidence: 99%